Adjunctive Intracoronal Splint in Periodontal Treatment: Report of Two Cases - Octavia, Mora; Soeroso, Yuniarti; Kemal, Yulianti; Airina, Airina (Journal of Dentistry Indonesia, 2014)
Reduction of the amount of tooth roots which are embedded in their periodontium could cause tooth mobility. Splinting a weaker tooth with a more stable one, and using the principle of the multiple-root stabilization is one way to overcome tooth mobility. Temporary splinting aims to prevent pathological migration, restore masticatory function, stabilize teeth before/after surgery, and evaluate the prognosis of periodontal treatment. The use of intracoronal splint is still controversial because there are only a few studies that have evaluated the effect of splinting on periodontal health. We report two cases to evaluate the effect of intracoronal splint on periodontal treatment. Two periodontal cases that use intracoronal splint before, during, and after periodontal regenerative therapy using bone graft. Causes of tooth mobility were removed and the splinting principles, terms and guidelines were mastered to get the maximum results of periodontal treatment. Both cases were evaluated radiographically 10 months after treatment. In these cases, intracoronal splint has supported the therapy before, during, or after surgery. Splinting is only for adjunctive therapy, and does not serve as the sole method in getting occlusal stability.